Investigating the thermostability, activation energy, and In vitro delivery of palm kernel cake enriched with synbiotic containing immobilized Lactiplantibacillus plantarum ATCC 8014 - Shaharuddin, Shahrulzaman; Mat Ropi, Anis Alysha; Zamri, Nur Ain Syuhada; Dos Mohamed, Abdul Manan; Abd Razak, Jeefferie; Kamaruding, Noor Azlina (Elsevier Ltd, 2023)
Feed additives play an important role in providing health benefits towards ruminant's production. The selection of probiotic encapsulation in pellet form gives limitation as probiotics are sensitive towards heat and delivery condition in a ruminant's stomach. Synbiotic encapsulation involves encapsulating probiotics with prebiotic ingredients to boost their viability. In this study, we investigated the best formulation of alginate (Alg) (3%, 4%, and 5%) and palm kernel cake (PKC) coating ratios (1:0, 1:1, and 1:1.5) for Lactiplantibacillus plantarum ATCC 8014 microencapsulation, through extrusion method. The optimum formulation was selected based on thermostability, physicochemical, morphological, and in vitro release properties. The unencapsulated probiotic (initial concentration of approximately 9.30 log CFU/mL) was the control sample in this study. The average microencapsulation efficiency for all samples was greater than 97%. The encapsulated probiotics (4% Alg-supplemented with 4% PKC) had the highest survival rates after heat exposure (99.33%) and in vitro release analysis (94.67%). The addition of alginate enhanced the roughness average significantly as well as increased the size. The activation energy showed that the sample without and with PKC utilized energy ranging from 254 to 200 kJ/kmol. K and 363–400 kJ/kmol. K, respectively. Thus, an optimized formulation of 4% Alg and a coating ratio of 1:1 may be able to prevent probiotic loss in industrial feed additives.